Russia and the Arab Spring: Foreign and domestic policy changes - Margarete Klein (Stiftung Wissenschaft und Politik (SWP), 2012)
The »Arab Spring« presents Russia with a dual challenge. On the one hand, while North Africa and the Middle East are undergoing a phase of upheaval, Moscow is looking to protect its interests in the region as well as its quest for great power status. Russia's failure in this sense in Libya caused it to defend its claims in Syria all the more vehemently. Conflicting views between Russia and Western states regarding the violent uprisings and conflicts in Libya and Syria are therefore both the cause and the consequence of the deteriorating relations between Russia and the West. On the other hand, the Arab Spring also serves as a domestic test of the »Putin System«. Its crisis of legitimacy had become apparent with the outbreak of mass demonstrations in December 2011
Keywords: 320